A novel uniplanar antenna with dual wideband characteristics for tablet/laptop applications. Issue 9 (16th July 2017) - Sim, Chow‐Yen‐Desmond; Chen, Chih‐Chiang; Li, Che‐Yu; Ge, Lei
Abstract: A novel uniplanar antenna design for tablet/laptop applications is proposed. The proposed antenna with a size of 68 × 12 × 0.8 mm 3 is comprised of three strip sections, namely, the feeding strip, parasitic shorted strip, and tuning stub strip (or printed LC matching circuit). Five resonant modes are induced by the proposed antenna, and they are combined to yield two wide operating bands that have 6‐dB return loss bandwidths of more than 50% (695‐1190 MHz and 1690‐2930 MHz). Thus, the proposed antenna can easily cover the entire LTE/WWAN operations working in the 698‐960 MHz and 1710‐2690 MHz bands. Besides demonstrating good radiation efficiency of more than 60% for the two wide operating bands, the proposed antenna also exhibits reduced ground effects, in which reducing the ground size will not deteriorate the antenna's performances.